2016
DOI: 10.1017/jfm.2016.435
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of large-scale free-stream turbulence with turbulent boundary layers

Abstract: The scale interactions occurring within a turbulent boundary layer are investigated in the presence of free-stream turbulence. The free-stream turbulence is generated by an active grid. The free stream is monitored by a single-component hot-wire probe while a second probe is roved across the height of the boundary layer at the same streamwise location. Large-scale structures occurring in the free-stream are shown to penetrate the boundary layer and increase the streamwise velocity fluctuations throughout. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
135
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(183 citation statements)
references
References 45 publications
46
135
2
Order By: Relevance
“…5 as a solid line. Previous studies have reported an increase in TBL skin friction under FST (Blair 1983;Hancock and Bradshaw 1989;Stefes and Fernholz 2004;Dogan et al 2016). Figure 3 confirms this trend with increasing FST.…”
Section: Reynolds Dependence and Self-similaritysupporting
confidence: 80%
See 4 more Smart Citations
“…5 as a solid line. Previous studies have reported an increase in TBL skin friction under FST (Blair 1983;Hancock and Bradshaw 1989;Stefes and Fernholz 2004;Dogan et al 2016). Figure 3 confirms this trend with increasing FST.…”
Section: Reynolds Dependence and Self-similaritysupporting
confidence: 80%
“…TBL transition was promoted by the addition of a trip wire at the leading edge of the flat plate where the TBL develops. The details of the experimental setup and motor schemes of the active grid can be found in Dogan et al (2016). The superscript + will denote quantities normalised with the friction velocity U , and the kinematic viscosity , as for instance in the wall-normal coordinate y + = yU ∕ , or the mean streamwise velocity U + = U∕U .…”
Section: Measurement Methods and Experimental Setupmentioning
confidence: 99%
See 3 more Smart Citations